Concentration of nitric oxide products in bronchoalveolar fluid obtained from infants who develop chronic lung disease of prematurity. Issue 3 (1st November 1999) - Vyas, Julian R; Currie, Andrew E; Shuker, David E G; Field, David J; Kotecha, Sailesh
Abstract : AIMS: To determine if nitric oxide (NO) products (nitrate and nitrite) are increased in bronchoalveolar lavage (BAL) fluid obtained from infants who develop chronic lung disease of prematurity (CLD). METHODS: One hundred and thirty six serial bronchoalveolar lavages were performed on 37 ventilated infants (12 with CLD, 18 with respiratory distress syndrome (RDS), and seven control infants) who did not receive inhaled NO. RESULTS: During the first week of life nitrate concentration was between 25–31 μmol/l in all three groups. Thereafter, the concentration of BAL fluid nitrate decreased to 14 μmol/l and 5.5 μmol/l, respectively in the RDS and control groups by 14 days of age. In contrast, nitrate in the CLD infants remained constant until 28 days of age (31.3 μmol/l at day 14; p<0.05). In all BAL fluid samples the mean concentration of nitrite was <1.2 μmol/l throughout the first 28 days with no significant differences noted among the three groups. CONCLUSION: The similar concentration of BAL fluid nitrate in all groups during the first week of life suggest that NO may be important in the adaptation of the pulmonary circulation after birth. However, persistence of nitrate in the BAL fluid of infants with CLD during the second week may reflect pulmonary maladaptation, or, more likely, persisting pulmonary inflammation.